Developing and implementing geofencing in destination alarm mobile application / Mohd Asraf Ayob - Ayob, Mohd Asraf (2015)
Dealing with daily-life can be much easier and interesting when technology can be integrated together. Geofencing as a GIS tool will help to notify people in specific area about any occurance event, news and information alerting. Advance technology has brought people to contribute in mobile application development scene. A very helpful mobile application can be develop with the integration of geo-fence for benefit of public transportation user. Through several phases of application development process, a user friendly mobile application integrated with geo-fence may become an important subject to daily life as people in the city mostly travel by public transportation and missing their destination due to take rest along the journey has become a problem. An alarm triggered when reaching nearly the destination might help to wake up and notify the desired destination.